Mulheres idosas na zona rural e sofrimento psíquico: um estudo sobre determinantes sociais da saúde - Prigol, Ana Paula (2024)
This research focuses on the psychological suffering of elderly women in rural areas and its relationship with the social determinants of health, that is, how these determinants interfere with the health of this population throughout life. The main objective of the study is to identify, from the point of view of elderly women in the rural area of ​​a small municipality in the state of Rio Grande do Sul, how the social determinants of health are linked to the psychological distress of these women. Specifically, we seek to understand the repercussions of social determinants on the lives of elderly women in rural areas; analyze the social determinants of health and psychological distress and describe the social determinants of health in their association with gender issues in rural areas. This is a qualitative, descriptive and field research, which was developed in the municipality of Lagoa Vermelha, Rio Grande do Sul. The study population was selected in a non-probabilistic way, for convenience and consisted of 9 elderly women from the community of Santa Luzia, in the interior of the municipality. Data collection took place through a focus group. The data was analyzed using the content analysis method. The research allowed the creation of two scientific productions. The first production aims to identify, from the point of view of elderly women living in rural areas, how the social determinants of health are linked to psychological distress. As an analytical concept, the Dahlgren and Whitehead model was used to explore the social determinants of health that are linked to psychological distress. The research identified causal elements of psychological distress, these were listed as risk and protective factors, subdivided into layers: macro determinants, intermediate, underlying and proximal determinants. The second production seeks to identify, based on the concept of intersectionality, the social markers present in the daily lives of elderly women in rural contexts, in their articulations with care, seeking to understand the relationship with the psychological suffering experienced by them. As an analytical concept, intersectionality was used to explore the markers of difference found in the research: age, gender and territory/work and how they are interconnected and overlapping in the production of inequality and illness in the face of care. The results showed that age, gender and territory/work are the social markers of difference considered central to thinking about the dynamism of articulations and the experiences of elderly women with care in the scenario of a rural community.